The Management of a Patient with Elevated Intraocular Pressure Resistant to Medical Treatment: Anterior Chamber Irrigation - Abdullah Beyoğlu; Şaban Gönül; Bengü Ekinci Köktekir; Şansal Gedik (Türk Oftalmoloji Dergisi)
A 7-year-old male patient was medically treated in another center for hyphema which occurred after blunt trauma to his right eye. He was admitted to our clinic when his visual acuity decreased after being discharged. Biomicroscopic examination revealed total hyphema. Intraocular pressure (IOP) was 48 mm Hg in the right eye with Goldmann applanation tonometry. Since IOP could not be managed by medical therapy and there was no regression in hyphema, anterior chamber was irrigated. As in our case, it should not be forgotten that re-hemorrhage may occur in the first week of hyphema during childhood. Moreover, surgical treatment should be considered when hemorrhage does not regress with medical treatment, increased IOP persists, and when there is a risk of corneal endothelial staining (corneal blood staining). (Turk J Ophthalmol 2014; 44: 400-2)